Frictionless contact between a rigid indentor and a transversely isotropic functionally graded layer - Patra, Rajesh; Barik, Sakti Pada; Chaudhuri, P.K. (Zielona Góra: Uniwersytet Zielonogórski)
This article is concerned with the study of frictionless contact between a rigid punch and a transversely isotropic functionally graded layer. The rigid punch is assumed to be axially symmetric and is supposed to be pressing the layer by an applied concentrated load. The layer is resting on a rigid base and is assumed to be sufficiently thick in comparison with the amount of indentation by the rigid punch.
Keywords: functionally graded material; transversely isotropic medium; Hankel transform; contact problem; Fredholm integral equation